2020
DOI: 10.1002/2211-5463.12970
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy under glucose starvation enhances protein translation initiation in response to re‐addition of glucose in C2C12 myotubes

Abstract: Cells starved of glucose for 24 h showed enhanced phosphorylation of p70S6K in response to re‐addition of glucose. Pharmacological inhibition studies revealed that autophagy under glucose starvation partially accounts for this effect. The results of the present study suggest that appropriate nutrient starvation can modulate cellular protein turnover and may be effective at improving muscle protein synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Similar to the anisomycin treatment above, this response was also dependent on the integrity of the S domain peptide motifs within ZAKα ( Figure 1 c). As a control for starvation-associated mTOR inhibition, we probed the phosphorylation state of S6 kinase (p-S6K) [ 25 ]. The arginines within the RGRYXXR/K motifs are subject to methylation [ 26 ] (phosphosite.org (accessed on 16 March 2023)).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the anisomycin treatment above, this response was also dependent on the integrity of the S domain peptide motifs within ZAKα ( Figure 1 c). As a control for starvation-associated mTOR inhibition, we probed the phosphorylation state of S6 kinase (p-S6K) [ 25 ]. The arginines within the RGRYXXR/K motifs are subject to methylation [ 26 ] (phosphosite.org (accessed on 16 March 2023)).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated autophagy events happening during glucose starvation in fission yeast. 62 These results suggest an activation of protease activity in the early stages of glucose starvation, possibly by the recognition of ubiquitinated substrates, which are then digested into peptides. 63 While earlier investigations also showed ubiquitination of ribosomal protein uS3 in budding yeast during rapid stress response, 64 additional analysis involving measurements of ubiquitination levels and enzymatic activity of the proteases could be done to validate our results in glucose starvation.…”
Section: Discussionmentioning
confidence: 88%
“…However, the TPCA profile of ribosomal proteins at 48 th hours of glucose deprivation are highly similar to data collected from samples without glucose deprivation suggesting resumption of translational activities. Previous studies had revealed system-wide attenuation in protein translation under glucose deprivation 36,37 that occurred independent of mRNA abundance 38 . Thus, the disassembly of ribosomes could possibly contribute or arise from decreased protein translation, an energy-intensive process 39,40 which prerequisite in many cells is the availability of glucose 37 .…”
Section: Resultsmentioning
confidence: 99%